The role of budget speech: a Malaysian government study - Ferry, Laurence; Zakaria, Zamzulaila; Eckersley, Peter (Emerald, 2014)
The purpose of this paper is to study the role of budget speech in the Malaysian Government as a “hybrid” for governing both the economy and social cohesion.Through archival research, a governmentality framework and the concept of hybrids (Miller et al., 2008) are employed to explore the role of budget speech in articulating ways in which the government managed the economic and social agenda.Previous governmentality studies have primarily been conducted on economic performance in western liberal democracies. Such research has illustrated the framework, measures undertaken by the government and choices of the governable person in actions for economic life. This paper applies these studies to a South East Asian context and finds that budget speeches between 2007 and 2011 are hybrids, in that they set out ways of achieving the two key priorities of post independence Malaysia – the need to promote economic development whilst also fostering social harmony. Most notably, it finds that economic development was the dominant priority in those budget speeches held prior to the global financial crisis and 2008 general election, whereas social cohesion assumed this position from 2009 onwards.The findings have both practical and social implications for Malaysia, but also other jurisdictions that are using budget speeches to try to promote economic reforms and foster social cohesion.